Geopolitika Chilében - Szilágyi, István (Magyar Agrár- és Élettudományi Egyetem Kaposvári Campus, felelős kiadó: Vörös Péter, 2012)
Geopolitics as a multidisciplinary branch of social science and as a theory of foreign policy appeared on the Latin-American continent in the second half of the 1920s. The main features they include are the next: aggressive approach to the space, the continental adaption of the organic state-theory elaborated by Ratzel and Kjellen, moreover, the developed geopolitical theory was thought to be converted into practice via the growing role of the army. In all Latin- American countries the armed forces and their various institutions became the scientific centre of elaborating the new attitude to the international relations as a theory. When the army az an institution assumed the political power, however, it was given an opportunity to put these theories into practice. With the definition of the constant and conjuntural national goals those countries of the vast territories aimed at both re-determination of their international economic and political positions and solving their problems connected with their own inner space. Therefore the regional transitions, the settling in the rarely- populated areas, the usage of sources of raw material and reserves, the control of transport and communication network of international significance and obtaining the influence over the new territories were the problems that in many of those countries came to the front. On the Latin-American continent the geopolitical schools with important theo-retical background were established in Argentina, Brazil and Chile. In this study we are going to introduce the Chilean geopolitical theory and practice established by generals Ramon Cañas Montalva and Augusto Pinochet. Apart from the theoretical outlines we will analyse the Chilean attitude to the possession of the Beagle-channel, The Drake-passage and the Magellan-strait and the Antarctic. Geopolitics as a multidisciplinary branch of social science and as a theory of foreign policy appeared on the Latin-American continent in the second half of the 1920s. The main features they include are ...